2013
DOI: 10.1523/jneurosci.2729-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 Inhibition Suppresses Tamoxifen Toxicity on CNS Glial Progenitor Cells

Abstract: It is increasingly apparent that treatment with a variety of anticancer agents often is associated with adverse neurological consequences. Clinical studies indicate that exposure even to tamoxifen (TMX), a putatively benign antihormonal agent widely used in breast cancer treatment, causes cognitive dysfunction and changes in CNS metabolism, hippocampal volume, and brain structure. We found that TMX is toxic for a variety of CNS cell populations in vitro and also increased cell death in the corpus callosum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Some research reported that BRAF mutation was closely related to the sensitivity of Selumetinib [ 30 ]. Chen found that Selumetinib selectively rescued primary glial progenitors from TMX toxicity, such as cognitive dysfunction and changes in CNS metabolism, hippocampal volume, and brain structure, in vitro while enhancing TMX effects on MCF7 [ 31 ]. MEK pathway also plays key role in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Some research reported that BRAF mutation was closely related to the sensitivity of Selumetinib [ 30 ]. Chen found that Selumetinib selectively rescued primary glial progenitors from TMX toxicity, such as cognitive dysfunction and changes in CNS metabolism, hippocampal volume, and brain structure, in vitro while enhancing TMX effects on MCF7 [ 31 ]. MEK pathway also plays key role in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation of TAM-induced toxicity at therapeutic doses in the brain revealed a loss of oligodendrocyte progenitor cells (OPCs) in the corpus callosum [ 7 ]. This was accompanied by a reduction in their proliferation, and that of neural progenitors in the subventricular zone and dentate gyrus, and it was suggested that this may represent a cellular substrate of cognitive dysfunction experienced by breast cancer patients receiving TAM therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in human brain structure and metabolism with TAM treatment have also been reported [ 5 ]. Yet, there has been surprisingly little work done in animal models to identify TAM-induced changes in structure or function of the nervous system (either central or peripheral) [ 6 ], although in one study it was associated with a loss of glial progenitor cells in the corpus callosum and with reduced cell division in neurogenic regions of the CNS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms to describe CICI development have been suggested such as genetic predisposition, hormonal changes, DNA damage secondary to increased oxidative stress, and increased levels of inflammatory cytokines (Ahles and Saykin, 2007;Argyriou et al, 2010). Impaired cognitive function accompanied by reduced hippocampal neurogenesis, loss of CNS progenitors (including glial progenitors), and myelinopathy secondary to clinically used chemotherapeutic agents in adult rodents have also been reported (Dietrich et al, 2006;Han et al, 2008;Monje, 2008;Briones and Woods, 2011;Christie et al, 2012;Chen et al, 2013a). The use of HDACi in cancer treatment has been demonstrated to prevent OPC differentiation; thus, HDACi may conceivably impact cognition as well.…”
Section: Introductionmentioning
confidence: 99%